1404. Twenty-year impact of Pneumococcal Conjugate Vaccines (PCV) on the burden of invasive pneumococcal disease in US children less than 5 years of age. (31st December 2020) - Lapidot, Rotem; Chapman, Ruth; Sutton, Kelly; Dillon-Murphy, Desmond; Patel, Shreeya; Chilson, Erica; Snow, Vincenza; Farkouh, Raymond; Wasserman, Matthew; Pelton, Stephen I
Abstract: Background: Clinical trials of PCV7 demonstrate significant reductions in vaccine-type (VT) invasive pneumococcal disease (IPD), clinically diagnosed pneumonia in children less than 5 years of age and VT acute otitis media in children < 2 years of age. Observational, population-based studies demonstrate a reduction in overall IPD in US children following the introduction of PCV7 and PCV13. The cumulative impact of PCV on IPD syndromes over the 20 years following introduction into the US national immunization program has not been detailed. Methods: Published and unpublished data from the Active Bacterial Core (ABC) surveillance network were used to calculate annual incidence rates of IPD and the proportional distribution by syndrome in children < 5 years of age. Cases averted were calculated from published incidence for each IPD syndrome and population data, for the pre-PCV, PCV7, and PCV13 eras. Cases averted over 2000-2009 were assumed due to PCV7 only, and those averted from 2010-2019 were assumed due to PCV13 only. It was assumed that in the absence of PCVs, disease incidence would have remained constant. Results: Annual cases of overall IPD, pneumococcal meningitis, and bacteremic pneumonia each declined more than 85% between the pre PCV7 incidence and the estimated incidence for 2019 (table 1). Overall, we estimated 282, 600 cases of IPD, including 30, 500 cases of meningitis and 78, 400 cases of bacteremic pneumonia were averted. We calculated a reduction of ~ 287, 600 VT cases of IPD minimally offset by an increase of ~5, 000 non-VT cases. Deaths per 100, 000 children < 5 years of age attributable to IPD declined by 67% in 2009 and by 64% in 2019 compared to 1997-1999. In total, 1, 628 deaths in children < 5 years were averted between 2000 and 2019. Table 1. Annual Cases of IPD by syndrome in US Children Less than 5 years of age Conclusion: The substantial public health impact of PCVs over the last two decades, as measured in cases and deaths averted in children less than 5 years, re-enforces the important role vaccines play in reducing the burden of serious disease in children. Disclosures: Rotem Lapidot, MD, MSCI, Pfizer (Consultant) Ruth Chapman, MSc, PhD, Evidera, Inc, (Evidera, Inc. received the funding to conduct this study.) (Consultant) Kelly Sutton, PhD, Evidera (Employee) Desmond Dillon-Murphy, MSc, PhD, Evidera, Inc. (Evidera, Inc. received the funding to conduct this study.) (Consultant) Shreeya Patel, PhD, Evidera, Inc, (Evidera, Inc. received the funding to conduct this study.) (Consultant) Erica Chilson, PharmD, Pfizer (Employee, Shareholder) Vincenza Snow, MD, Pfizer (Employee) Raymond Farkouh, PhD, Pfizer (Employee) Matthew Wasserman, MSc., Pfizer Inc. (Employee) Stephen I. Pelton, MD, Merck vaccine (Consultant, Grant/Research Support)Pfizer (Consultant, Grant/Research Support)Sanofi Pasteur (Consultant, Other Financial or Material Support, DSMB)Seqirus Vaccine Ltd. (Consultant)